Adquisición, registro y transmisión en tiempo real de señales sismológicas bajo TCP/IP - Vargas-jiménez, Carlos A.; Castellanos, G.; Flórez, J. A.; Gómez, J. P. (Earth Sciences Research Journal, 2001)
The constant evolution of network technologies has made possible the development of applications facilitating the real time access to the information. This way, it is possible the implementation of remote monitoring systems that using PCs achieves efficient transmission of signals through computer networks. In this work, the procedures system design and implementation procedures are explain in Client/Server environment that, based on TCP/lP, transmits in real time 16 seismological signals over LAN network and the Internet. The server is a PC endowed with an acquisition data card and it is the one in charge of carrying out the signal Analog/Digital conversion, to store in files those that correspond to seismic events and, at the same time, to assist the applications of the different clients. The client's software allows the users to view in real time the signals that the server is acquiring and to carry out a basicn processing to the signals that have been registered in the server.